Administrative resources and the efficiency of school administration of educational personnel Ban Tha Fang School, Muang District, Prachuap Khiri Khan Province - Kaewjamsai, Tinnapob; Wiwatchankit, Sopee; Kumhom, Naitawan (RATANABUTH JOURNAL, 2022)
The objectives of this research were 1) to study the level of administrative resources of educational personnel. Ban Tha Fang School, Muang District, Prachuap Khiri Khan Province 2) To study the level of educational institution administration efficiency of educational personnel. Ban Tha Fang School, Muang District, Prachuap Khiri Khan Province, and 3) to study the relationship of administrative resources and the efficiency of school administration of educational personnel at Ban Tha Fang School, Mueang District, Prachuap Khiri Khan Province. The population used in the research consisted of 30 people. The research instruments were questionnaires, statistical data analysis, percentage, mean, standard deviation. and Pearson’s correlation coefficient test. The results of the research were as follows: 1) The level of relationship between administrative resources and the efficiency of school administration of educational personnel. When considering each aspect, it was found that it was at the highest level. Sort by lot to less, including academic administration General administration and Personnel management 2) The level of relationship between administrative resources, money and management efficiency. The positive correlation was at a moderate level. Sorted in descending order from highest to lowest, i.e. academic administration. General administration budget management and personnel management 3) the relationship between administrative resources material and equipment with management efficiency the positive correlation was at a moderate level. Sorted in descending order, namely, academic administration. General administration budget management and personnel management 4) the relationship between administrative resources Management with management efficiency the positive correlation was at a moderate level. Sorted in descending order, namely, academic administration. General administration budget management and personnel management.